Role of Borderless Higher Education for Refugees programme in offering high quality teacher education and training for refugees in Dadaab settlement in Kenya - Etich E. J., Kirui Kipng; Osman, Ahmed (Advances in Social Sciences Research Journal, 2016)
The quality of refugee education across the world is wanting. Teacher quality for all in refugee camps/settlements is difficult to achieve in many countries that host refugees. Reason is because most international agencies that come to aid of the refugees are mostly concerned with basic humanitarian assistance like health, food and shelter. But teacher quality is a key determinant of students’ participation rates and achievement levels. It also remains an important ingredient towards attainment of social justice in terms of equity in educational quality for students. One contributing factor to teacher quality is professional training and education though its availability and quality create inequity for many refugee teachers in their camps. This paper describes how Borderless Higher Education for Refugees (BHER) initiative is improving access, equity, and quality in professional training and education of refugee un-trained volunteer teachers in Dadaab refugee settlement schools in north eastern Kenya.